Variable transmittance optical laminate, method for producing same, and smart window including same
The variable transmittance optical laminate addresses the issue of fixed transmittance in conventional window systems by eliminating the need for a separate substrate and incorporating a functional coating layer, resulting in a more durable and defect-resistant optical laminate with improved light management capabilities.
Patent Information
- Application Number
- JP2024555142
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-03-24
- Filing Date
- 2023-03-09
- Publication Date
- 2025-04-11
AI Technical Summary
Conventional transportation and household window systems have fixed transmittance levels, leading to issues such as glare during the day and inadequate light in low-light conditions, as well as potential defects like light leakage and cracks in the optical laminate.
A variable transmittance optical laminate is developed without a separate substrate for forming the conductive layer, ensuring the sealant height matches the liquid crystal height, and incorporating a functional coating layer with a surface hardness of 3B to 8H to minimize defects and maintain constant optical hue.
The solution simplifies the manufacturing process, reduces the risk of light leakage and defects, and improves the durability of the optical laminate by maintaining a consistent sealant and liquid crystal layer height, while also enhancing the flexibility and durability of the laminate.
Smart Images

Figure 2025509752000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a variable transmittance optical laminate, a method for producing the same, and a smart window including the same. [Background technology]
[0002] In general, an external light blocking coating is often applied to glass windows of vehicles and other means of transport. However, the glass windows of conventional means of transport have a fixed transmittance, and the external light blocking coating also has a fixed transmittance. Therefore, the windows of such conventional means of transport have a fixed overall transmittance, which may lead to accidents. For example, if the overall transmittance is set low, there is no problem during the day when there is sufficient light in the surroundings. However, in the case of nighttime when there is insufficient light in the surroundings, there is a problem that the driver, etc., has difficulty in properly checking the surroundings of the means of transport. Alternatively, if the overall transmittance is set high, there is a problem that the driver, etc., may be dazzled during the day when there is sufficient light in the surroundings. In addition, in the case of household fittings, an external light blocking coating may be applied, but in this case, as in the case of the windows of the above-mentioned means of transport, the transmittance is fixed, and it is not easy to adjust the amount of light entering the room. For this reason, a variable transmittance optical laminate capable of changing the transmittance of light when a voltage is applied has been developed.
[0003] The variable transmittance optical stack is driven by applying a voltage to drive the liquid crystal to change the transmittance. The variable transmittance optical stack developed to date is manufactured by forming a conductive layer for driving the liquid crystal on a separate substrate and combining it with other elements such as a polarizer, and may further include an insulating layer in some cases.
[0004] In the case of Korean Patent Publication No. 10-2226630, a light control film that can be used for electronic blinds that control the transmission of external light is provided, in which the Vickers hardness value Xs of the spacer is 16.9 to 40.2 and the Vickers hardness value Xf of the second laminate is 11.8 to 35.9. However, the member corresponding to the sealant is not suitable for supporting the liquid crystal layer, and as a result, the optical laminate and the smart window including the same may suffer from light leakage or cracks or scratches, which may cause defects in the optical laminate.
[0005] Therefore, there is a need to develop a variable transmittance optical laminate that simplifies the manufacturing process by not including a separate substrate layer for forming a conductive layer, ensures that the height of the sealant is the same as the height of the liquid crystal, maintains a constant optical color within the plane, and minimizes liquid crystal defects. Summary of the Invention [Problem to be solved by the invention]
[0006] An object of the present invention is to provide a variable transmittance optical laminate that does not require a separate substrate for forming a conductive layer, and thus has a simplified manufacturing process.
[0007] Another object of the present invention is to provide a variable transmittance optical laminate, in which the surface hardness of the functional coating layers contained in the polarizing plate is 3B to 8H, and the total thickness of each functional coating layer is 2 to 50 μm.
[0008] Another object of the present invention is to provide a variable transmittance optical laminate including a sealant having a height of 2 to 20 μm after curing.
[0009] Another object of the present invention is to provide a variable transmittance optical laminate in which the height of the liquid crystal layer and the height of the sealant are substantially the same.
[0010] Another object of the present invention is to provide a variable transmittance optical laminate that includes a functional layer that can improve surface hardness, thereby minimizing cracks or scratches that occur during processing.
[0011] Another object of the present invention is to provide a smart window including the variable transmittance optical laminate, and a fitting for an automobile or building to which the smart window is applied.
[0012] However, the problems to be solved by the present invention are not limited to those mentioned above, and other problems not mentioned will be clearly understood by those skilled in the art from the following description. [Means for solving the problem]
[0013] The present invention relates to a liquid crystal layer including a sealant; a first polarizing plate including a first functional coating layer and positioned on one side of the liquid crystal layer; a second polarizing plate including a second functional coating layer and positioned on the other side of the liquid crystal layer; a first transparent conductive layer formed between the first polarizing plate and the liquid crystal layer; and a second transparent conductive layer formed between the second polarizing plate and the liquid crystal layer, wherein at least one of the first transparent conductive layer and the second transparent conductive layer is formed in direct contact with one of the first polarizing plate and the second polarizing plate, each of the first functional coating layer and the second functional coating layer has a surface pencil hardness of 3B to 8H, and a total thickness of the first functional coating layer and the second functional coating layer is 2 to 50 μm.
[0014] In the first aspect of the present invention, the sealant may have a height of 2 to 20 μm after curing.
[0015] In the second aspect of the present invention, the first functional coating layer and the second functional coating layer may each have a thickness of 1 to 35 μm.
[0016] In a third aspect of the present invention, the first functional coating layer and the second functional coating layer may include at least one of a hard coating layer and a low refractive index layer.
[0017] In a fourth aspect of the present invention, the hard coating layer may contain an acrylate compound or an epoxy compound.
[0018] In a fifth aspect of the present invention, the low refractive index layer may contain one or more selected from the group consisting of SiO2, Al2O3, MgF2, CaF2 and cryolite.
[0019] In a sixth aspect of the present invention, at least one of the first transparent conductive layer and the second transparent conductive layer may be formed in direct contact with one of the first polarizing plate and the second polarizing plate without the use of a separate substrate between the transparent conductive layer and the first polarizing plate and the second polarizing plate.
[0020] In a seventh aspect of the present invention, at least one of the first transparent conductive layer and the second transparent conductive layer may include an easy-adhesion layer between either one of the first polarizing plate and the second polarizing plate and be formed in direct contact with the either one of the first polarizing plate and the second polarizing plate.
[0021] In an eighth aspect of the present invention, at least one of the first transparent conductive layer and the second transparent conductive layer may contain one or more materials selected from the group consisting of transparent conductive oxides, metals, carbon-based materials, conductive polymers, conductive inks, and nanowires.
[0022] In a ninth aspect of the present invention, at least one of the first polarizing plate and the second polarizing plate may include one or more layers selected from the group consisting of a protective layer, a phase difference adjusting layer, and a refractive index adjusting layer.
[0023] In a tenth aspect of the present invention, at least one of the first polarizing plate and the second polarizing plate may have a thickness of 30 to 200 μm.
[0024] In an eleventh aspect of the present invention, the liquid crystal layer may include one or more spacers selected from the group consisting of ball spacers and column spacers.
[0025] In a twelfth aspect of the present invention, the spacer may have a height of 2 to 20 μm.
[0026] In a thirteenth aspect of the present invention, an area occupied by the spacer in the liquid crystal layer may be 0.01% to 10% of an area of the liquid crystal layer.
[0027] In a fourteenth aspect of the present invention, the variable transmittance optical laminate may further include one or more layers selected from the group consisting of a pressure-sensitive adhesive layer, an ultraviolet absorbing layer, and an impact resistant layer.
[0028] The present invention also relates to a method for producing the variable transmittance optical laminate. The present invention also relates to a smart window comprising the variable transmittance optical laminate.
[0029] The present invention also relates to a means of transportation comprising said smart window. The present invention also relates to an automobile in which the smart window is applied to one or more of a front window, a rear window, a side window, a sunloop window, and an interior partition.
[0030] The present invention also relates to a wearable device including the smart window.
[0031] The present invention also relates to a building fixture including the smart window. Effect of the Invention
[0032] According to the variable transmittance optical laminate of the present invention, the hardness of the polarizer hard coating layer, i.e., the functional coating layer, satisfies the range of 3B to 8H, and the total thickness of the first polarizer and the second polarizer is 2 to 50 μm, thereby ensuring a sealant height of 2 to 20 μm, and making the sealant height the same as the liquid crystal thickness improves the sealant's pressing phenomenon and spreading property, prevents light leakage between the liquid crystal layer and other substrates, and maintains a constant optical color in the plane.
[0033] In addition, the variable transmittance optical laminate according to the present invention is free from cracks and has excellent durability, thereby minimizing defects in the optical laminate and smart window.
[0034] According to the variable transmittance optical laminate of the present invention, the process of forming a conductive layer on a substrate and then bonding it to other components required for forming a conventional optical laminate can be omitted, and the manufacturing process can be simplified compared to the conventional optical laminate.
[0035] In addition, according to the variable transmittance optical laminate of the present invention, a conductive layer is formed directly on one side of a polarizing plate, and a separate substrate for forming the conductive layer is not required, so that the thickness can be significantly reduced compared to conventional optical laminates.
[0036] In addition, according to the variable transmittance optical laminate of the present invention, a conductive layer is formed directly on one side of a polarizing plate, and a separate substrate for forming the conductive layer is not included, so that the transmittance in the light transmission mode can be improved compared to conventional optical laminates.
[0037] In addition, the variable transmittance optical laminate according to the present invention includes a functional layer capable of improving surface hardness, thereby minimizing cracks or scratches that occur during processing compared to conventional optical laminates. [Brief description of the drawings]
[0038] [Figure 1] FIG. 1 is a diagram showing a layered structure of a variable transmittance optical layered body according to an embodiment of the present invention. [Diagram 2] FIG. 2 is a diagram showing a layered structure of a variable transmittance optical layered body according to another embodiment of the present invention. [Diagram 3] FIG. 3 is a diagram showing a laminated structure of a smart window for a vehicle according to an embodiment of the present invention. [Figure 4] FIG. 4 is a diagram showing a layered structure of a smart window for architectural fittings according to one embodiment of the present invention. [Diagram 5] FIG. 5 is a diagram showing a layered structure of a smart window for architectural fittings according to another embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0039] The present invention relates to a variable transmittance optical laminate that can minimize cracks that occur during processing and can form the height of a sealant to be substantially the same as the height of a liquid crystal layer by making the sealant height 20 μm or less.
[0040] More specifically, the present invention relates to a variable transmittance optical laminate including a liquid crystal layer including a sealant, a first polarizing plate including a first functional coating layer and positioned on one side of the liquid crystal layer, a second polarizing plate including a second functional coating layer and positioned on the other side of the liquid crystal layer, a first transparent conductive layer formed between the first polarizing plate and the liquid crystal layer, and a second transparent conductive layer formed between the second polarizing plate and the liquid crystal layer, wherein at least one of the first transparent conductive layer and the second transparent conductive layer is formed in direct contact with one of the first polarizing plate and the second polarizing plate, and the first functional coating layer and the second functional coating layer each have a surface pencil hardness of 3B to 8H, and the total thickness of the first functional coating layer and the second functional coating layer is 2 to 50 μm.
[0041] The variable transmittance optical laminate of the present invention is particularly suitable for technical fields in which light transmittance can be changed by applying a voltage, and can be used, for example, as a smart window. A smart window refers to an optical structure that changes light transmittance by applying an electric signal to control the amount of light or heat passing through. That is, a smart window is provided so that it can be changed to a transparent, opaque, or translucent state by applying a voltage, and is also called a variable transmittance glass, a light control glass, or a smart glass. A smart window may be used as a partition for dividing the interior space of a vehicle or building or for privacy protection, or as a daylight window disposed in an opening of a building. It may also be used as a highway sign, a bulletin board, a scoreboard, a clock, or an advertising screen, and can be used to replace glass in a vehicle such as a window or sunroof of a car, a bus, an airplane, a ship, or a train. The variable transmittance optical laminate of the present invention can also be used in smart windows in the various technical fields described above, but since the conductive layer is directly formed on the polarizing plate, no separate substrate is required for forming the conductive layer, and therefore the thickness is thin and the bending characteristics are advantageous, and the variable transmittance optical laminate of the present invention can be particularly suitably used in smart windows for vehicles or buildings. In one or more embodiments, the smart window to which the variable transmittance optical laminate of the present invention is applied can be used in transportation, for example, front windows, rear windows, side windows, and sunroof windows of automobiles, or building fixtures, and can be used for dividing the interior space of automobiles or buildings, such as interior partitions, or for privacy protection, in addition to blocking external light, and can also be used in wearable devices such as helmets, glasses, or watches.
[0042] Hereinafter, the embodiments of the present invention will be described in more detail with reference to the drawings. However, the following drawings attached to this specification are intended to illustrate preferred embodiments of the present invention and to facilitate a better understanding of the technical concept of the present invention together with the above-mentioned invention content, and therefore the present invention should not be interpreted as being limited only to the matters described in these drawings. The terms used in this specification are intended to describe the embodiments and are not intended to limit the present invention.
[0043] In this specification, the singular form includes the plural form unless otherwise specified in the phrase. For example, the term "polarizer" used in this specification may mean at least one of the first and second polarizers, the term "transparent conductive layer" may mean at least one of the first and second transparent conductive layers, and the term "functional coating layer" may mean at least one of the first and second functional coating layers.
[0044] As used herein, the terms "comprises" and / or "comprising" are used in a sense that does not exclude the presence or addition of one or more other components, steps, operations and / or elements other than the stated components, steps, operations and / or elements. The same reference numerals refer to the same components throughout the specification.
[0045] Spatially relative terms such as "below," "bottom," "lower," "upper," "top," and the like can be used to easily describe the relationship of one element or component to another element or component as shown in the drawings. Spatially relative terms should be understood to include different orientations of elements in use or operation in addition to the orientation shown in the drawings. For example, if an element shown in the drawings is turned upside down, an element described as "below" or "below" another element may be placed "above" the other element. Thus, the exemplary term "below" can include both an orientation below and above. Elements can be oriented in other directions, and thus the spatially relative terms can be interpreted accordingly. As used herein, "planar direction" can be interpreted as a direction perpendicular to the polarizer and / or transparent conductive layer, i.e., a direction viewed from the user's viewing side.
[0046] As used in this specification, "substantially" can be interpreted to include not only being completely identical or identical physically, but also being within the range of error in measurement or manufacturing processes, for example, an error range of 0.1% or less.
[0047] <Variable transmittance optical laminate and method for producing same> Referring to FIG. 1, the variable transmittance optical laminate according to an embodiment of the present invention may include a first polarizer 100-1, a second polarizer 100-2, a first transparent conductive layer 200-1, a second transparent conductive layer 200-2, and a liquid crystal layer, and the liquid crystal layer may include a transmittance control layer 300, an alignment film 400, and a sealant 500. Referring to FIG. 2, the variable transmittance optical laminate according to another embodiment of the present invention may further include an adhesive layer 600 on the outermost surface of the laminate. More specifically, referring to FIG. 3 to FIG. 5, the first polarizer 100-1 and the second polarizer 100-2 each include a polarizer 110 and at least one functional coating layer 120 for improving the surface hardness of the polarizer, and in one or more embodiments, may include an adhesive layer 600 and glass 700 and 800.
[0048] Polarizing Plate The first polarizing plate 100-1 and the second polarizing plate 100-2 may be referred to as a polarizing plate 100 in this specification. The polarizing plate 100 includes a polarizer 110 and a functional coating layer 120, and may further include a protective layer, a phase difference control layer, and a refractive index control layer in one or more embodiments.
[0049] Polarizer The polarizer 110 may be any conventional or later developed polarizer, such as a stretched type polarizer or a coated type polarizer.
[0050] In one embodiment, the stretched polarizer may include a stretched polyvinyl alcohol (PVA) resin. The polyvinyl alcohol resin may preferably be a polyvinyl alcohol resin obtained by saponifying a polyvinyl acetate resin. Examples of the polyvinyl acetate resin include polyvinyl acetate, which is a homopolymer of vinyl acetate, and copolymers of vinyl acetate and other monomers copolymerizable therewith. The other monomers may be unsaturated carboxylic acid, unsaturated sulfonic acid, olefin, vinyl ether, and acrylamide monomers having an ammonium group. The polyvinyl alcohol resin may be modified, for example, polyvinyl formal or polyvinyl acetal modified with aldehydes.
[0051] In some embodiments, the liquid crystal layer may be formed by applying a liquid crystal coating composition to one side of the protective film. The liquid crystal coating composition may include a reactive liquid crystal compound and a dichroic dye.
[0052] The reactive liquid crystal compound may include a monomer molecule that includes a reactive mesogen (RM) capable of expressing liquid crystallinity and a polymerizable terminal functional group, and has a liquid crystal phase after a crosslinking reaction by heat or light. The reactive liquid crystal compound may be polymerized by light or heat to form a polymer network while maintaining the liquid crystal alignment. By utilizing the reactive liquid crystal compound, a thin film polarizer that maintains the optical anisotropy and dielectric constant characteristics of the liquid crystal and has improved mechanical and thermal stability may be formed.
[0053] The dichroic dye is a component contained in the liquid crystal coating composition that imparts polarization properties, and has a property that the absorbance in the long axis direction of the molecule is different from the absorbance in the short axis direction. Non-limiting examples of the dichroic dye may include acridine dyes, oxazine dyes, cyanine dyes, naphthalene dyes, azo dyes, anthraquinone dyes, etc. These may be used alone or in combination of two or more.
[0054] The liquid crystal coating composition further includes a solvent capable of dissolving the reactive liquid crystal compound and the dichroic dye, and may include, for example, propylene glycol monomethyl ether acetate (PGMEA), methyl ethyl ketone (MEK), xylene, chloroform, etc. The liquid crystal coating composition may further include a labeling agent, a polymerization initiator, etc., within a range that does not impair the polarization properties of the coating film.
[0055] Functional Coating Layer Referring to FIGS. 3 to 5, the functional coating layer 120 may be provided to improve the hardness of the polarizing plate 100. As shown in FIG.
[0056] In general, the optical laminate included in the smart window has a tendency that the transmittance becomes higher or the driving voltage becomes lower as the height of the liquid crystal layer becomes lower. Therefore, reducing the thickness of the liquid crystal layer, preferably manufacturing it to be 20 μm or less, is advantageous in terms of suppressing the light leakage phenomenon and improving reliability. However, in the manufacturing process of the optical laminate, after applying the sealant, in the process of bonding the upper laminate and the lower laminate, the surface of the laminate base material is pressed by the sealant, so that the height of the sealant is not reduced to 20 μm or less, and the height of the liquid crystal layer adjacent to the sealant exceeds 20 μm, which causes a problem of light leakage or a decrease in the reliability of the spacer. In addition, when trying to solve the above problem by reducing the viscosity of the sealant material and reducing the thickness of the sealant, there are problems such as difficulty in maintaining the uniformity of the sealant line at a constant level, reduced adhesion, and liquid crystal contamination inside the sealant.
[0057] In order to solve the above-mentioned technical problems, the present invention has a technical feature that the functional coating layer is included to provide a polarizing plate with a certain hardness, thereby suppressing the phenomenon of the surface of the substrate being pressed during the sealant application and bonding process, and making it possible to manufacture the sealant at a thickness of 20 μm or less. By manufacturing the sealant at a thickness of 20 μm or less, the sealant and the liquid crystal layer are made to have substantially the same thickness, which not only effectively suppresses the light leakage phenomenon in the liquid crystal region adjacent to the sealant, but also improves the reliability of the spacer.
[0058] The functional coating layer is not particularly limited as long as it can impart a predetermined hardness to the polarizing plate in order to solve the above-mentioned technical problems, and may include, for example, a hard coating layer and / or a low refractive index layer.
[0059] The hard coating layer may be a conventional or later developed hard coating layer. In one or more embodiments, the hard coating layer may include an acrylate compound or an epoxy compound, and may further include inorganic fine particles, a photoinitiator, and the like.
[0060] The acrylate-based compound may include a monomer or oligomer containing a (meth)acrylate group, and the term "(meth)acryl-" as used herein means "methacryl-", "acryl-" or both. Non-limiting examples of the acrylate-based compound include neopentyl glycol acrylate, 1,6-hexanediol (meth)acrylate, propylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, trimethylolethane tri(meth)acrylate, 1,2,4-cyclohexane tetra(meth)acrylate, pentaglycerol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, pentaerythritol tri(meth)acrylate, and dipentaerythritol tri(meth)acrylate. Examples of the acrylates include bis(2-hydroxyethyl)isocyanurate di(meth)acrylate, hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxybutyl (meth)acrylate, isooctyl (meth)acrylate, iso-dexyl (meth)acrylate, stearyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, phenoxyethyl (meth)acrylate, and isoborneol (meth)acrylate. These may be used alone or in combination of two or more. The acrylate compound may include an epoxy (meth)acrylate compound and / or a urethane (meth)acrylate compound.
[0061] The epoxy compound may include a monomer or oligomer having at least one epoxy group in the molecule. The epoxy group may be an alicyclic epoxy group. The alicyclic ring included in the epoxy group may have 3 to 7 carbon atoms, for example, an alicyclic epoxy group including a cyclohexane ring (cyclohexyl epoxy). The alicyclic ring may have a substituent. For example, the alicyclic ring may include an alkyl substituent having 1 to 20 carbon atoms. If the alkyl substituent has more than 20 carbon atoms, it may be disadvantageous in terms of curing speed. The alkyl substituent may be a straight-chain or branched type, and if it is a branched type, the number of carbon atoms may be 3 or more.
[0062] According to an embodiment of the present invention, in the method for producing a hard coating, the hard coating composition may include inorganic fine particles. According to an embodiment of the present invention, the inorganic fine particles may be inorganic fine particles having a nano-scale particle size, for example, nano-particles having a particle size of 100 nm or less, or 10 to 100 nm, or 10 to 50 nm. Furthermore, the inorganic fine particles may be, for example, silica fine particles, aluminum oxide particles, titanium oxide particles, or zinc oxide particles. By including the inorganic fine particles, the hardness of the hard coating layer can be further improved. According to an embodiment of the present invention, the inorganic fine particles may be included in an amount of 10 to 60 parts by weight, or 20 to 50 parts by weight, based on 100 parts by weight of the hard coating composition. By including the inorganic fine particles in the above range, the hardness of the hard coating layer can be improved by adding the inorganic fine particles within a range that does not deteriorate the physical properties of the composition for forming a hard coating layer.
[0063] According to an embodiment of the present invention, in the method for preparing a hard coating, the hard coating composition may include a photoinitiator, which may include, but is not limited to, 1-hydroxy-cyclohexyl-phenyl ketone, 2-hydroxy-2-methyl-1-phenyl-1-propanone, 2-hydroxy-1-[4-(2-hydroxyethoxy)phenyl]-2-methyl-1-propanone, methylbenzoyl formate, α,α-dimethoxy-α-phenylacetophenone, 2-benzoyl-2-(dimethylamino-)-1-[4-(4-morpholinyl)phenyl]-1-butanone, 2-methyl-1-[4-(methylthio)phenyl]-2-(4-morpholinyl)-1-propanone diphenyl(2,4,6-trimethylbenzoyl)-phosphine oxide, or bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide. In addition, examples of products currently available on the market include Irgacure 184, Irgacure 500, Irgacure 651, Irgacure 369, Irgacure 907, Darocur 1173, Darocur MBF, Irgacure 819, Darocur TPO, Irgacure 907, Esacure KIP 100F, etc. These photoinitiators may be used alone or in combination of two or more different types.
[0064] According to an embodiment of the present invention, the photoinitiator may be included in an amount of 0.5 to 10 parts by weight, preferably 1 to 5 parts by weight, based on 100 parts by weight of the hard coating composition. When the photoinitiator is in this range, sufficient cross-linking photopolymerization can be achieved without deteriorating the physical properties of the hard coating layer.
[0065] Meanwhile, in the method for producing a hard coat film according to the present invention, the hard coating composition may further contain additives commonly used in the technical field to which the present invention belongs, such as a surfactant, an anti-yellowing agent, a labeling agent, or an antifouling agent, in addition to the above-mentioned components. The content of the additives is not particularly limited, since it can be variously adjusted within a range that does not deteriorate the physical properties of the hard coating composition according to the present invention.
[0066] The low refractive index layer may be provided to improve the hardness of the polarizing plate within the scope of the present invention. The low refractive index layer may contain one or more low refractive index agents selected from the group consisting of SiO2, Al2O3, MgF2, CaF, and cryloite, and in some embodiments, may contain the compound or resin used in the hard coating layer.
[0067] The hard coating layer and the low refractive index layer may be used alone or in some embodiments, may be used as a multi-layer structure. The functional coating layer 120 may be formed in direct contact with one surface of the polarizer 110 as shown in FIG. 3 to FIG. 5, but is not limited thereto. For example, when the polarizer includes a retardation control layer and / or a refractive index control layer, the functional coating layer may be formed on one surface of the retardation control layer and / or the refractive index control layer described later, and the functional coating layer, the retardation control layer, the refractive index control layer, and the polarizer may be sequentially laminated. The functional coating layer 120 is preferably formed on the liquid crystal layer side of the polarizer 110, i.e., on the inner side of the polarizer. For example, the first functional coating layer 120-1 and the second functional coating layer 120-2 may be provided on the inner sides of the first polarizer 110-1 and the second polarizer 110-2, respectively, and may be arranged to face each other. In this case, the functional coating layer not only provides a level of hardness suitable for forming components such as a transparent conductive layer on the polarizing plate, thereby minimizing cracks or scratches that occur during the manufacturing or processing process of the optical laminate, but also has the advantage of more effectively preventing the surface of the substrate from being pressed by the sealant, thereby reducing the thickness of the sealant.
[0068] In one embodiment, the functional coating layer 120 preferably has a surface pencil hardness of 3B to 8H. The surface pencil hardness may be measured by placing a pencil on the surface of the functional coating layer at a 45° angle using a pencil hardness tester (manufactured by SUKBO Science Co., Ltd., Korea), applying a load of 750 g, and scratching the functional coating layer with the pencil at a speed of 300 mm / min, or by using a Mitsubishi product, applying 5 times per pencil hardness, and heat treating at 100° C. for 10 minutes, and evaluating whether scratches are visually confirmed. When the surface pencil hardness of the functional coating layer satisfies the above range, it is possible to further improve the bending resistance or durability of the optical laminate as well as having excellent abrasion resistance.
[0069] In one or more embodiments, the first functional coating layer 120-1 and the second functional coating layer 120-2 may each have a thickness of 1 to 35 μm, more preferably 5 to 25 μm, and the total thickness of the first functional coating layer 120-1 and the second functional coating layer 120-2 may be 2 to 50 μm. The thickness may refer to the thickness after drying, and when the total thickness of the first functional coating layer 120-1 and the second functional coating layer 120-2 satisfies the above range, a hard coating film that has excellent hardness, can be thinned, and hardly generates a curling phenomenon can be manufactured. In addition, there is also an advantage in that the thickness of the sealant can be reduced by more effectively suppressing the phenomenon that the surface of the substrate is pressed by the sealant.
[0070] Specifically, the functional coating layer can be applied by a suitable method such as a die coater, an air knife, a reverse roll, a spray, a blade, a casting, a gravure, a microgravure, or a spin coating.
[0071] protective layer The protective layer is for preserving the polarization characteristics of the polarizer from post-processing and external environments, and may be implemented in the form of a protective film, etc. The protective layer may be formed on one or both sides of the polarizer in direct contact therewith, but is not limited thereto. For example, the protective layer may be used as a multi-layer structure in which one or more protective layers are continuously stacked, or may be formed in direct contact with another member such as a retardation adjusting layer. In one or more embodiments, the protective layer may include one or more selected from the group consisting of polyethylene terephthalate (PET), polyethylene isophthalate (PEI), polyethylene naphthalate (PEN), polybutylene terephthalate (PBT), diacetyl cellulose, triacetyl cellulose (TAC), polycarbonate (PC), polyethylene (PE), polypropylene (PP), polymethyl acrylate (PMA), polymethyl methacrylate (PMMA), polyethyl acrylate (PEA), polyethyl methacrylate (PEMA), and cyclic olefin polymer (COP). The thickness of the protective layer may be from 10 to 100 μm, more preferably from 20 to 80 μm.
[0072] In addition, the protective layer may further include an ultraviolet absorbing agent on the outermost surface to prevent deterioration of the function of the optical laminate. The ultraviolet absorbing layer is not particularly limited as long as it is used to prevent deterioration of the optical laminate due to ultraviolet rays, and examples thereof include salicylic acid-based ultraviolet absorbers (phenyl salicylate, p-tert-butyl salicylate, etc.), benzophenone-based ultraviolet absorbers (2,4-dihydroxybenzophenone, 2,2'-dihydroxy-4,4'-dimethoxybenzophenone, etc.), benzotriazole-based ultraviolet absorbers (2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)benzotriazole, 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-3'-(3',4',5' ',6''-Tetrahydrophthalimidomethyl)-5'-methylphenyl)benzotriazole, 2,2-methylenebis(4-(1,1,3,3-tetramethylbutyl)-6-(2H-benzotriazol-2-yl)phenol), 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-3'-tert-butyl-5'-(2-octyloxycarbonylethyl)-phenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-3'-(1-methyl-1-phenylethyl)-5'-(1,1,3,3-tetramethylbuty 2-(2H-benzotriazol-2-yl)-6-(linear and branched dodecyl)-4-methylphenol, mixture of octyl-3-[3-tert-butyl-4-hydroxy-5-(chloro-2H-benzotriazol-2-yl)phenyl]propionate and 2-ethylhexyl-3-[3-tert-butyl-4-hydroxy-5-(5-chloro-2H-benzotriazol-2-yl)phenyl]propionate, etc.), cyanoacrylate UV absorbers (2'-ethylhexyl-2-cyano-3,3-diphenylacrylate, ethyl-2-cyano-3-(3',4'-methylenedioxyphenyl)-acrylate, triazine-based ultraviolet absorbers, etc. may be used, and benzotriazole-based ultraviolet absorbers and triazine-based ultraviolet absorbers, which are highly transparent and have an excellent effect of preventing deterioration of the polarizing plate and the transmittance variable layer, are preferred, and benzotriazole-based ultraviolet absorbers with a more suitable spectral absorption spectrum are particularly preferred. The benzotriazole-based ultraviolet absorbers may be bis(Bis)-modified, for example, 6,6'-methylenebis(2-(2H-benzo[d][1,2,3]triazol-2-yl)-4-(2,4,4-trimethylpentan-2-yl)phenol), 6,6'-methylenebis(2-(2H-benzo[d][1,2,3]triazol-2-yl)-4-(2-hydroxyethyl)phenol), etc.,
[0073] Phase difference adjustment layer The retardation control layer is for complementing the optical properties of the optical laminate and may be embodied in the form of a retardation film, etc., or may be a conventional or later developed retardation film. For example, a quarter wave plate (1 / 4 wave plate) or a half wave plate (1 / 2 wave plate) for delaying the phase of light may be used, and these may be used alone or in combination. The retardation control layer may be formed on one surface of a polarizer in direct contact therewith, but is not limited thereto. For example, the retardation control layer may be formed on one surface of a protective layer in direct contact therewith, or may be formed on one surface of a refractive index control layer in direct contact therewith.
[0074] The retardation control layer may be a polymer stretched film or a liquid crystal polymer film obtained by stretching a polymer film capable of imparting optical anisotropy by stretching in an appropriate manner. In one embodiment, the polymer stretched film may be a polymer layer including a polyolefin such as polyethylene (PE) or polypropylene (PP), a cycloolefin polymer (COP) such as polynorbornene, polyvinyl chloride (PVC), polyacrylonitrile (PAN), polysulfone (PSU), acryl resin, polyester such as polycarbonate (PC) or polyethylene terephthalate (PET), polyacrylate, polyvinyl alcohol (PVA) or triacetyl cellulose (TAC) or a cellulose ester polymer, or a copolymer of two or more monomers among the monomers forming the polymer. The method for obtaining the polymer stretched film is not particularly limited, and for example, the polymer material is molded into a film and then stretched. The method for forming the film is not particularly limited, and the film can be formed by known methods such as injection molding, sheet molding, blow molding, injection blow molding, inflation molding, extrusion molding, foam molding, and cast molding, and secondary processing methods such as compressed air molding and vacuum molding may also be used. Among them, extrusion molding and cast molding are preferably used. At this time, for example, an unstretched film can be extruded using an extruder equipped with a T-die, a circular die, or the like. When obtaining a molded product by extrusion molding, a material in which various resin components, additives, etc. have been melt-kneaded in advance can be used, or the product can be molded through melt-kneading during extrusion molding.In addition, various resin components may be dissolved using a solvent common to various resin components, such as chloroform, methylene dichloride, etc., and then cast-dried and solidified to form an unstretched film. The polymer stretched film may be uniaxially stretched in the mechanical direction (MD; mechanical direction, lengthwise or longitudinal direction) and uniaxially stretched in the transverse direction (TD; transverse direction, widthwise or width direction) of the mechanical direction. A biaxially stretched film may be produced by stretching the formed film using a sequential biaxial stretching method of roll stretching and tenter stretching, a simultaneous biaxial stretching method using tenter stretching, a biaxial stretching method using tubular stretching, or the like. The liquid crystal polymer film may contain a reactive liquid crystal compound in a polymerized state. The reactive liquid crystal compound may be similarly applied to the reactive liquid crystal compound of the coating type polarizer described above. In one or more embodiments, the thickness of the retardation control layer may be 10 to 100 μm in the case of a polymer stretched film, and 0.1 to 5 μm in the case of a liquid crystal polymer film.
[0075] Refractive index adjustment layer The refractive index adjustment layer is provided to compensate for the refractive index difference of the optical laminate caused by the transparent conductive layer 200, and may play a role of improving the visibility by reducing the refractive index difference. The refractive index adjustment layer may also be provided to correct the hue caused by the transparent conductive layer 200. Meanwhile, when the transparent conductive layer has a pattern, the refractive index adjustment layer can compensate for the transmittance difference between the patterned region where the pattern is formed and the non-patterned region where the pattern is not formed. Specifically, the transparent conductive layer 200 is stacked adjacent to another member (e.g., a polarizer, etc.) having a different refractive index, and a difference in light transmittance may be induced due to the refractive index difference with the adjacent layer. In particular, when a pattern is formed on the transparent conductive layer, a problem may occur in which the patterned region and the non-patterned region are visually distinguishable. Therefore, by including the refractive index adjustment layer, the refractive index is compensated, and the difference in light transmittance of the optical laminate can be reduced, and in particular, when a pattern is formed on the transparent conductive layer, the patterned region and the non-patterned region are visually distinguishable. In one embodiment, the refractive index of the refractive index adjustment layer may be appropriately selected depending on the material of the adjacent other member, and may be preferably 1.4 to 2.6, and more preferably 1.4 to 2.4. In this case, it is possible to prevent light loss due to a sharp refractive index difference between the other member and the transparent conductive layer 200. The refractive index adjustment layer is not particularly limited as long as it can prevent a sharp refractive index difference between the transparent conductive layer 200 and another member such as a polarizer, and may be formed from a compound used in forming a conventional or later developed refractive index adjustment layer, for example, a refractive index adjustment layer forming composition including a polymerizable isocyanurate compound.
[0076] In one embodiment, the polarizing plate 100 may further include other components to supplement or strengthen the properties of the polarizer in addition to the above-mentioned components, for example, may further include an overcoat layer to further improve mechanical durability. In one or more embodiments, the polarizing plate 100 may have a thickness of 30 to 200 μm, preferably 30 to 170 μm, and more preferably 50 to 150 μm. In this case, the polarizing plate 100 can be used to manufacture an optical laminate having a thin thickness while maintaining optical properties.
[0077] Transparent conductive layer The transparent conductive layer 200 is provided for driving the liquid crystal layer and may be formed in direct contact with the polarizer 100. For example, as shown in FIG. 1, the first transparent conductive layer 200-1 and the second transparent conductive layer 200-2 may be formed in direct contact with the first polarizer 100-1 and the second polarizer 100-2, respectively. Conventional optical laminates used in manufacturing smart windows and the like are manufactured by forming a conductive layer for driving liquid crystal on one side of a substrate and bonding the other side of the substrate to a polarizer. However, the variable transmittance optical laminate according to the present invention is characterized in that it does not include a separate substrate for forming a conductive layer, but directly forms a conductive layer on one side of a polarizer, thereby reducing the thickness of the laminate and improving the transmittance and bending characteristics in a light transmission mode. In one embodiment, the transparent conductive layer 200 may be formed by direct deposition on one side of the polarizer 100. In this case, the transparent conductive layer 200 may be formed in direct contact with the pretreated surface of the polarizer 100 after a pretreatment such as a corona treatment or a plasma treatment is performed on one surface of the polarizer 100 in order to improve adhesion to the polarizer 100. The pretreatment is not limited to a corona treatment or a plasma treatment, and any pretreatment process may be used as long as it does not impair the object of the present invention. In another embodiment, the transparent conductive layer 200 may be formed in direct contact with the polarizer 100 via an easy-adhesion layer (not shown) provided on one surface of the polarizer 100 in order to improve adhesion to the polarizer 100. The transparent conductive layer 200 preferably has a visible light transmittance of 50% or more, and may include, for example, one or more selected from the group consisting of transparent conductive oxide, metal, carbon-based material, conductive polymer, conductive ink, and nanowire, but is not limited thereto, and any conventional or later developed transparent conductive layer material may be used. The conductive layer may also be configured to have a structure of two or more layers by combining the above materials. For example, the conductive layer may include a two-layer structure of a metal layer and a transparent conductive oxide layer, thereby reducing the reflectance of incident light and increasing the transmittance. The metal layer has a high reflectance and may reduce the visibility of the screen when used alone, but the reflectance can be reduced and the transmittance can be improved by stacking a transparent conductive oxide layer.
[0078] More specifically, in one or more embodiments, the transparent conductive oxide may include one or more selected from the group consisting of indium tin oxide (ITO), indium zinc oxide (IZO), indium zinc tin oxide (IZTO), aluminum zinc oxide (AZO), gallium zinc oxide (GZO), florin tin oxide (FTO), zinc oxide (ZnO), etc. The metal may include one or more selected from the group consisting of gold (Au), silver (Ag), copper (Cu), aluminum (Al), platinum (Pt), palladium (Pd), chromium (Cr), titanium (Ti), tungsten (W), niobium (Nb), tantalum (Ta), vanadium (V), iron (Fe), manganese (Mn), cobalt (Co), nickel (Ni), zinc (Zn), and alloys containing at least one of these, for example, a silver-palladium-copper (APC) alloy or a copper-calcium (CuCa) alloy. The carbon-based material may include at least one selected from the group consisting of carbon nanotubes (CNTs) and graphene, and the conductive polymer may include at least one selected from the group consisting of polypyrrole, polythiophene, polyacetylene, PEDOT, and polyaniline. The conductive ink may be an ink in which a metal powder and a curable polymer binder are mixed, and the nanowire may be, for example, a silver nanowire (AgNW).
[0079] The transparent conductive layer 200 may be formed in a two-layer structure by combining the above materials. For example, the transparent conductive layer 200 may be formed in a two-layer structure including a metal layer and a transparent conductive oxide layer to reduce the reflectance of incident light and increase the transmittance. The transparent conductive layer 200 may be formed by a method commonly used in the art, and may be formed by selecting an appropriate process from coating processes such as spin coating, roller coating, bar coating, dip coating, gravure coating, curtain coating, die coating, spray coating, doctor coating, and kneader coating; printing processes such as screen printing, spray printing, inkjet printing, relief printing, intaglio printing, and planographic printing; deposition processes such as CVD (chemical vapor deposition), PVD (physical vapor deposition), and PECVD (plasma enhanced chemical vapor deposition), and dry or wet plating processes.
[0080] Liquid crystal layer The liquid crystal layer can change the driving mode of the optical laminate by controlling the transmittance of light incident from one or more directions by an electric field. The liquid crystal layer may include a liquid crystal compound in the transmittance control layer 300, or may include an alignment film 400. For example, the liquid crystal layer may be located in a space provided by a sealant 500 and a spacer (not shown) provided between the first polarizer 100-1 and the second polarizer 100-2 in the light control region. The liquid crystal compound is not particularly limited as long as it can control the transmittance of light by being driven by an electric field, and may be a conventional or later developed liquid crystal compound. For example, the contents regarding the reactive liquid crystal compound of the coating type polarizer described above may be applied in the same manner. The liquid crystal behavior mode of the liquid crystal layer is not particularly limited, and may be driven in a twisted nematic (TN) mode, a super twisted nematic (STN) mode, a vertical alignment (VA) mode, or the like.
[0081] Sealants The sealant 500 may be located between the first polarizer 100-1 and the second polarizer 100-2 in the inactive region. The sealant may serve to bond the first polarizer and the second polarizer, and may also secure a space between the first polarizer and the second polarizer together with a spacer to provide a liquid crystal compound.
[0082] The sealant 500 may include a curable resin as a base resin. The base resin may be an ultraviolet curable resin or a thermosetting resin known in the art to be used for sealants. The ultraviolet curable resin may be a polymer of an ultraviolet curable monomer. The thermosetting resin may be a polymer of a thermosetting monomer. The base resin of the sealant 500 may be, for example, an acrylate-based resin, an epoxy-based resin, a urethane-based resin, a phenol-based resin, or a mixture of the above resins. In one embodiment, the base resin may be an acrylate-based resin, and the acrylate-based resin may be a polymer of an acrylic monomer. The acrylic monomer may be, for example, a multifunctional acrylate. In another embodiment, the sealant may further include a monomer component in the base resin. The monomer component may be, for example, a monofunctional acrylate. In another embodiment, the sealant may further include a monomer component in the base resin. The monomer component may be, for example, a monofunctional acrylate. In the present specification, a monofunctional acrylate may mean a compound having one acrylic group, and a polyfunctional acrylate may mean a compound having two or more acrylic groups. The curable resin may be cured by irradiation with ultraviolet light and / or heating. The ultraviolet irradiation conditions or heating conditions may be appropriately set within a range that does not impair the object of the present application. The sealant may further include an initiator, for example, a photoinitiator or a thermal initiator, as necessary. The sealant 500 may be formed by a method commonly used in the art, for example, by drawing the sealant on the outer edge (i.e., non-active area) of the liquid crystal layer using a dispenser equipped with a nozzle.
[0083] The sealant may have a height after curing that is substantially the same as the height of the liquid crystal layer, for example, 2 to 20 μm, in which case, as described above, light leakage from the liquid crystal layer region adjacent to the sealant does not occur, and the reliability of the spacer can be further improved.
[0084] Spacer The spacer (not shown) serves to maintain a constant liquid crystal gap in the liquid crystal layer and may include at least one of a ball spacer and a column spacer, and is particularly preferably a ball spacer in terms of processability. The number of spacers may be one or more, and it is preferable that the spacer has a height of 2 to 20 μm in order to support the liquid crystal layer. Also, when viewed in a planar direction, it is preferable that the area of the spacer in the liquid crystal layer is 0.01 to 10% of the area of the liquid crystal layer in terms of improving user visibility and transmittance in a light-transmitting mode.
[0085] Other functional layers The variable transmittance optical laminate of the present invention may further include other components within the scope of the present invention, for example, may further include an adhesive layer 600 (see Figures 2 to 5), and may further include an ultraviolet absorbing layer (not shown) and an impact resistant layer (not shown).
[0086] The adhesive layer 600 may be formed using an adhesive or a pressure-sensitive adhesive, and preferably has an appropriate adhesive strength so that peeling or bubbles do not occur when the optical laminate is handled, as well as transparency and thermal stability, and may have point elasticity properties applicable to smart windows. The adhesive may be a conventional adhesive or an adhesive to be developed in the future, for example, a photocurable adhesive. The photocurable adhesive is crosslinked and cured by receiving active energy rays such as ultraviolet rays (UV) and electron beams (EB) to exhibit strong adhesive strength, and may be composed of reactive oligomers, reactive monomers, photopolymerization initiators, etc. The reactive oligomer is an important component that determines the properties of the adhesive, and forms a polymer bond by photopolymerization to form a cured coating. Examples of reactive oligomers that can be used include polyester-based resins, polyether-based resins, polyurethane-based resins, epoxy-based resins, polyacrylic resins, and silicone-based resins. The reactive monomer acts as a crosslinker and diluent for the reactive oligomer, and affects the adhesive properties. Examples of the reactive monomer that can be used include monofunctional monomers, polyfunctional monomers, epoxy monomers, vinyl ethers, and cyclic ethers. The photopolymerization initiator absorbs light energy to generate radicals or cations to initiate photopolymerization, and may be selected and used appropriately depending on the photopolymerization resin. The adhesive may be a conventional or later developed adhesive, and in one or more embodiments, an acrylic adhesive, a rubber adhesive, a silicone adhesive, a urethane adhesive, a polyvinyl alcohol adhesive, a polyvinylpyrrolidone adhesive, a polyacrylamide adhesive, a cellulose adhesive, a vinyl alkyl ether adhesive, or the like may be used.
[0087] The pressure-sensitive adhesive is not particularly limited as long as it has adhesive strength and viscoelasticity, but in terms of availability, it may be preferably an acrylic pressure-sensitive adhesive, for example, one that contains a (meth)acrylate copolymer, a crosslinking agent, and a solvent, etc. The crosslinking agent may be a conventional or later developed crosslinking agent, for example, one that contains a polyisocyanate compound, an epoxy resin, a melamine resin, a urea resin, a dialdehyde, a methylol polymer, etc., and preferably one that contains a polyisocyanate compound. The solvent may include a typical solvent used in the field of resin compositions, such as alcohol compounds such as methanol, ethanol, isopropanol, butanol, and propylene glycol methoxy alcohol; ketone compounds such as methyl ethyl ketone, methyl butyl ketone, methyl isobutyl ketone, diethyl ketone, and dipropyl ketone; acetate compounds such as methyl acetate, ethyl acetate, butyl acetate, and propylene glycol methoxy acetate; cellosolve compounds such as methyl cellosolve, ethyl cellosolve, and propyl cellosolve; and hydrocarbon compounds such as hexane, heptane, benzene, toluene, and xylene. These may be used alone or in combination of two or more.
[0088] The thickness of the adhesive layer 600 may be appropriately determined depending on the type of resin acting as an adhesive, adhesive strength, and the environment in which the adhesive is used. In one embodiment, the adhesive layer may have a thickness of 0.1 to 500 μm, preferably 0.5 to 450 μm, and more preferably 1 to 400 μm, in order to ensure sufficient adhesive strength and minimize the thickness of the optical laminate, and in the case of an adhesive layer, may have a thickness of 2 to 30 μm, preferably 3 to 20 μm, and more preferably 5 to 10 μm. In one embodiment, the adhesive layer 600 may be formed on one or both sides of the polarizing plate by lamination or vacuum bonding.
[0089] The ultraviolet absorbing layer (not shown) is not particularly limited as long as it is for preventing deterioration of the optical laminate due to ultraviolet rays, and the contents of the ultraviolet absorber described in the protective layer can be applied as is, so the description will be omitted.
[0090] The impact-resistant layer (not shown) is not particularly limited as long as it is located in the inward direction and functions to absorb the impact and prevent damage to the internal structure when an impact is applied to the entire surface of the window, and is preferably a material having a high tolerance to deformation energy, such as a thermoplastic resin with high toughness. Examples of such resins include polycarbonate-based resins, polyimide-based resins, polyamide-based resins, polyamideimide-based resins, and polyester-based resins. In addition, since the present invention is intended to be used in a display device, it is preferable to use a resin that is excellent in light transmission, preferably optically transparent.
[0091] <Smart Window> The present invention includes a smart window including the variable transmittance optical laminate, an automobile in which the smart window is applied to at least one of a front window, a rear window, a side window, a sunroof window, and an interior partition, and a building fixture including the smart window. For example, an automobile including a smart window of the present invention may be one in which an automobile glass 700 is bonded to both sides of an optical laminate including a polarizing plate 100, a transparent conductive layer 200, a liquid crystal layer, and a tacky adhesive layer 600 (see FIG. 3), and may be manufactured by, for example, placing an adhesive film and an automobile glass on both sides of the optical laminate, and then heating at a temperature of 90° C. and a vacuum state of about 1 bar for 10 to 20 minutes using a press machine, and the adhesive film may include an EVA film, a PVB film, etc. In addition, the optical laminate may have building fittings (fitting glass) 800 bonded to both sides (see FIG. 4) or one side (see FIG. 5) of it, or fitting glass may be applied to both sides of the optical laminate and bonded, and then UV cured to produce a smart window product for fittings having the same configuration as in FIG. 4 or FIG. 5, or fitting glass may be bonded to one side of the optical laminate using a lamination method to produce a smart window product for fittings having the same configuration as in FIG. 4 or FIG. 5.
[0092] In addition, the smart window may be applied to means of transportation and wearable devices commonly used in the field. EXAMPLES
[0093] Hereinafter, the present invention will be described in detail with reference to the embodiments. However, the present invention is not limited to the embodiments disclosed below, and may be embodied in various different forms. However, the embodiments are provided to fully disclose the present invention and to fully inform those skilled in the art of the present invention of the scope of the invention, and the present invention is defined only by the scope of the claims.
[0094] Manufacturing example 1: Production of polarizing plates (1) Swelling treatment process A 60 μm thick polyvinyl alcohol film (raw film) (manufactured by Kuraray Co., Ltd., product name "Kuraray Poval Film VF-PE#6000", average polymerization degree 2400, saponification degree 99.9 mol%) was continuously unwound from a raw roll and transported, and immersed in a swelling bath containing pure water at 20°C for 30 seconds. In this swelling process, inter-roll stretching (longitudinal uniaxial stretching) was performed with a difference in peripheral speed between the nip rolls. The stretching ratio based on the raw film was 2.5 times.
[0095] (2) Dyeing process Next, the film that had passed through the nip rolls was immersed in a dye bath at 30° C. with a mass ratio of pure water / potassium iodide / iodine / boric acid of 100 / 2 / 0.01 / 0.3 for 120 seconds. In this dyeing treatment, roll-to-roll stretching (longitudinal uniaxial stretching) was also performed with a difference in peripheral speed between the nip rolls. The stretching ratio was 1.1 times based on the film after the swelling treatment step.
[0096] (3) Crosslinking process Next, the film that had passed through the nip roll was immersed in a first crosslinking bath at 56° C., in which the mass ratio of pure water / potassium iodide / boric acid was 100 / 12 / 4, for 70 seconds. Roll-to-roll stretching (longitudinal uniaxial stretching) was performed with a difference in peripheral speed between the nip roll and a nip roll provided between the first crosslinking bath and the second crosslinking bath. The stretching ratio was 1.9 times based on the film after the dyeing process.
[0097] (4) Complementary color processing process Next, the film after the crosslinking treatment was immersed for 10 seconds in a second crosslinking bath at 40° C. containing potassium iodide / boric acid / pure water (mass ratio) of 9 / 2.9 / 100.
[0098] (5) Cleaning process Next, the film after the second crosslinking treatment was immersed in a cleaning bath containing pure water at 14°C for 5 seconds, and the shower volume was 5 m 3 / h and shower temperature 14°C.
[0099] (6) Drying process Next, the film after the washing process was passed through a drying oven and heated and dried at 80°C for 190 seconds to produce a polarizer film. The moisture content after drying was 13.6%, and the thickness of the obtained polarizer film was about 21 μm.
[0100] (7) Joining process Next, a water-based adhesive containing 5 parts by weight of polyvinyl alcohol per 100 parts by weight of water was prepared as an adhesive. Then, protective films were laminated on both sides of the polarizer film using the prepared UV adhesive. The obtained laminate was exposed to UV light to harden the adhesive, and polarizing plates were produced.
[0101] The thickness of the adhesive layer in the obtained polarizing plate was about 2 μm. Production Example 2: Production of hard coating layer forming composition HC1 A hard coating composition HC1 was prepared by mixing 16.2 g of a dendrimer compound (Miwan Specialty Chemical, SP-1106), 14.4 g of inorganic nanoparticles (Nissan Chemical, MEK-AC-2140, solid content 40 wt%), 1.8 g of a multifunctional (meth)acrylate containing an ethylene glycol group (Nippon Kayaku, DPEA126), 0.7 g of a photoinitiator (1-hydroxycyclohexyl phenyl ketone), and 2.9 g of methyl ethyl ketone.
[0102] Production Example 3: Production of hard coating layer forming composition HC2 18% by weight of ethylene glycol group-containing multifunctional acrylate DPEA-12 (manufactured by Nippon Kayaku Co., Ltd.), 12% by weight of cyclohexyl group-containing multifunctional urethane acrylate SOU-1700B (manufactured by SHIN-A T&C Co., Ltd.), 20% by weight of silica inorganic nanoparticles Nanopol-784 (50% dilution with normal butyl acetate, 20 nm, manufactured by Evonik Co., Ltd.), 1.8% by weight of Irgacure 184 (manufactured by BASF Co., Ltd.), 0.2% by weight of BYK-333 (manufactured by BYK Chemie Co., Ltd.), 38% by weight of methyl ethyl ketone, and 10% by weight of normal butyl acetate were mixed to produce a hard coating composition HC2.
[0103] Manufacturing Example 4: Formation of hard coating layer The hard coating composition prepared in Preparation Example 2 or Preparation Example 3 was dried on one side of the polarizing plate prepared in Preparation Example 1, and the thickness was adjusted using a Mayer Bar to coat it. The hard coating composition was then dried at 80° C. for 5 minutes, and then exposed to a high-pressure mercury lamp at 500 mJ / m 2 The upper and lower polarizing plates were each formed with a hard coating layer on one surface by curing with an amount of light of 1000 nm.
[0104] Production Example 5: Production of transparent conductive layer The upper and lower polarizing plates manufactured through Preparation Examples 1 to 4 were inserted, 450W DC power was applied to operate the sputtering gun, and plasma was then induced to the ITO (10wt% Sn doped In2O3) target to form a transparent conductive film (90nm). The formed transparent conductive film was ion-treated by operating an ion gun with 50W DC power. At this time, the pressure was maintained at 3mTorr at room temperature, and argon gas and oxygen gas were supplied at 30sccm and 1sccm, respectively. At this time, the ITO thickness was measured by FT-SEM.
[0105] Manufacturing Example 6: Fabrication of alignment film An alignment liquid was coated on the ITO surfaces of the upper and lower polarizers prepared in Preparation Example 5, and then dried (80° C. / 2 min.) After that, UV was irradiated onto the dried alignment liquid to prepare an alignment film.
[0106] Manufacturing Example 7: Spacer Spread Manufacturing The mixed solvent was prepared by mixing ball spacers (SP series, manufactured by SEKISUI) with 100 ml of IPA according to the height of each liquid crystal gap in the following examples. Then, the conductive layer laminate of the lower polarizer of Preparation Example 6 was placed in a spacer sprayer (SDSS-KHU02, SHINDO ENG LAB), and the prepared mixed solvent was sprayed at 110°C and dried for 20 minutes to form ball spacers on the alignment film of the lower polarizer.
[0107] Production Example 8: Production of sealant layer A sealant (UVF-006, 70,000 mPa s, Sekisui) was applied to the outer periphery of the lower polarizing plate manufactured in Manufacturing Example 6 using a sealant dispenser (SHOT mini 200Ωx, Musashi) according to the product size. Then, with the polarization axes of the upper and lower polarizing plates arranged parallel to each other at 0° or 90°, liquid crystal was injected onto the alignment film of the upper polarizing plate using the ODF process to bond the upper and lower polarizing plates. Then, UV curing (500 mJ / cm) was performed along the sealant line. 2 ) was carried out.
[0108] Examples 1 to 8 and Comparative Examples 1 to 7: Production of optical laminates Variable transmittance optical laminates for smart windows according to Examples 1 to 8 and Comparative Examples 1 to 7 were manufactured according to the compositions shown in Tables 1 to 2 below.
[0109] [Table 1]
[0110] [Table 2]
[0111] Experimental Example (1)Pencil hardness The pencil hardness of the hard-coated surface of the polarizing plate was measured using a pencil hardness tester (manufactured by SUKBO Science Co., Ltd., Korea). The polarizing plate was bonded to a 80 mm x 60 mm glass using an adhesive. Then, a pencil (manufactured by Mitsubishi Co., Ltd.) was placed on the hard-coated surface at a 45° angle, and a 750 g weight was applied to scratch the surface with the pencil at a speed of 300 mm / min, five times per pencil hardness, and the hardness was measured based on whether scratches occurred for each pencil hardness after heat treatment at 100°C for 10 minutes. The results are shown in Tables 3 and 4 below.
[0112] (2) Thickness measurement The measurements were made using a thickness gauge (MH-15M, SENDAI NIKON). The thickness, height, and width of the hard coating layer of the polarizing plate, the liquid crystal gap, and the sealant at the same positions before and after preparation were measured and calculated to confirm the results. The results are shown in Tables 3 and 4 below.
[0113] (3) Evaluation of reliability of mandrels In order to evaluate bending properties and cracking properties using a cylindrical bending tester (Lab-Q D605, manufactured by CKSI), a 100mm x 100mm optical laminate sample with upper and lower plates bonded was placed on a 4mm diameter iron bar so that the lower plate surface of the polarizer was in contact with the iron bar, and a 1kg load was applied to the outside of the bent part in a bent state, and the sample was placed in a 90℃ oven for 2 hours, and then placed at room temperature and the bent area was observed to check for the occurrence of cracks. The results are shown in Tables 3 and 4 below.
[0114] <Evaluation criteria> - 0 cracks: Good - 1 or more cracks: defective
[0115] [Table 3]
[0116] [Table 4]
[0117] Referring to the experimental data in Tables 3 and 4, in the case of Examples 1 to 8 in which the variable transmittance optical laminate according to the embodiment of the present invention is applied, the pencil hardness of the hard coating surface of the first polarizer and the second polarizer is measured at 3B to 8H, the total thickness of the first functional coating layer and the second functional coating layer is 2 to 50 μm, and the thickness of the liquid crystal layer and the height of the sealant are observed to be the same as 2 to 20 μm. In contrast, in the case of Comparative Examples 1 to 7 deviating from the present invention, the pencil hardness or the total thickness of the first functional coating layer and the second functional coating layer is lower or exceeds the range proposed in the present invention. In particular, in the case of Comparative Examples 1, 2, 4, and 5 in which both polarizers do not include a hard coating layer, the height of the sealant is observed to be higher than the thickness of the liquid crystal layer. In addition, in Comparative Example 6 in which the pencil hardness of the hard coating surface of the polarizer is below the range proposed in the present application, and Comparative Example 7 in which the total thickness of the first functional coating layer and the second functional coating layer exceeds 50 μm, it is observed that there is a difference between the thickness of the liquid crystal layer and the height of the sealant. In such a case, the reliability of the optical laminate may be reduced, such as light leakage between the liquid crystal layer and other substrates. In the evaluation of the reliability mandrel, cracks were observed in Comparative Examples 1 to 7, whereas no cracks were observed in Examples 1 to 8 according to the present invention. In particular, in the case of Comparative Example 3, in which the pencil hardness and the total thickness of the first and second functional coating layers exceeded the ranges proposed in the present invention, cracks were observed even though there was no difference between the thickness of the liquid crystal layer and the height of the sealant.
[0118] Therefore, the variable transmittance optical laminate and the smart window including the same according to the present invention have a hardness of the first functional coating layer and the second functional coating layer that satisfies the range of 3B to 8H, and the total thickness of the first functional coating layer and the second functional coating layer is 2 to 50 μm, so that the height of the sealant after hardening is 2 to 20 μm, and it is possible to ensure the same height of the sealant as the thickness of the liquid crystal layer, which is 20 μm or less, and therefore it has been confirmed that the laminate has excellent durability without cracking. [Industrial Applicability]
[0119] According to the variable transmittance optical laminate of the present invention, the hardness of the polarizer hard coating layer, i.e., the functional coating layer, satisfies the range of 3B to 8H, and the total thickness of the first polarizer and the second polarizer is 2 to 50 μm, thereby ensuring a sealant height of 2 to 20 μm, and making the sealant height the same as the liquid crystal thickness improves the sealant's pressing phenomenon and spreading property, prevents light leakage between the liquid crystal layer and other substrates, and maintains a constant optical color in the plane. [Explanation of symbols]
[0120] 100-1, 100-2: Polarizing plate 110-1, 110-2: Polarizer 120-1, 120-2: Functional coating layer 200-1, 200-2: Transparent conductive layer 300: Transmittance adjustment layer 400-1, 400-2: Alignment film 500: Sealant 600:Adhesive layer 700: Car glass 800: Glass for building materials
Claims
1. a liquid crystal layer including a sealant; a first polarizing plate including a first functional coating layer and positioned on one side of the liquid crystal layer; a second polarizing plate including a second functional coating layer and positioned on the other side of the liquid crystal layer; a first transparent conductive layer formed between the first polarizer and the liquid crystal layer; a second transparent conductive layer formed between the second polarizer and the liquid crystal layer; At least one of the first transparent conductive layer and the second transparent conductive layer is formed in direct contact with one of the first polarizing plate and the second polarizing plate, the first functional coating layer and the second functional coating layer each have a surface pencil hardness of 3B to 8H; The total thickness of the first functional coating layer and the second functional coating layer is 2 to 50 μm.
2. 2. The variable transmittance optical stack of claim 1, wherein the sealant has a height of 2 to 20 μm after curing.
3. The variable transmittance optical stack according to claim 1 , wherein the first and second functional coating layers each have a thickness of 1 to 35 μm.
4. The variable transmittance optical laminate according to claim 1 , wherein the first functional coating layer and the second functional coating layer each include at least one of a hard coating layer and a low refractive index layer.
5. The variable transmittance optical stack of claim 4 , wherein the hard coating layer comprises an acrylate-based compound or an epoxy compound.
6. The low refractive index layer is made of SiO 2 , Al 2 O 3 , MgF 2 , CaF 2 5. The variable transmittance optical stack according to claim 4, comprising at least one selected from the group consisting of: and cryolite.
7. 2. The variable transmittance optical laminate of claim 1, wherein at least one of the first transparent conductive layer and the second transparent conductive layer is formed in direct contact with one of the first polarizer and the second polarizer without using a separate substrate between the transparent conductive layer and the first polarizer and the second polarizer.
8. The variable transmittance optical laminate of claim 1 , wherein at least one of the first transparent conductive layer and the second transparent conductive layer is formed in direct contact with one of the first polarizing plate and the second polarizing plate via an easy-adhesion layer between the transparent conductive layer and the first polarizing plate and the second polarizing plate.
9. 2. The variable transmittance optical laminate of claim 1, wherein at least one of the first transparent conductive layer and the second transparent conductive layer comprises at least one selected from the group consisting of transparent conductive oxides, metals, carbon-based materials, conductive polymers, conductive inks, and nanowires.
10. 2. The variable transmittance optical laminate according to claim 1, wherein at least one of the first polarizing plate and the second polarizing plate includes at least one selected from the group consisting of a protective layer, a phase difference adjusting layer, and a refractive index adjusting layer.
11. The variable transmittance optical laminate of claim 1 , wherein at least one of the first polarizing plate and the second polarizing plate has a thickness of 30 to 200 μm.
12. The variable transmittance optical laminate according to claim 1, wherein the liquid crystal layer includes at least one spacer selected from the group consisting of a ball spacer and a column spacer.
13. The variable transmittance optical stack according to claim 12, wherein the spacer has a height of 2 to 20 μm.
14. The variable transmittance optical stack according to claim 12, wherein the area of the spacer in the liquid crystal layer is 0.01% to 10% of the area of the liquid crystal layer.
15. The variable transmittance optical laminate according to claim 1 , further comprising at least one layer selected from the group consisting of an adhesive layer, an ultraviolet absorbing layer, and an impact resistant layer.
16. A method for producing the variable transmittance optical laminate according to any one of claims 1 to 15.
17. A smart window comprising the variable transmittance optical laminate according to any one of claims 1 to 15.
18. A means of transportation comprising the smart window of claim 17.
19. 18. A car comprising the smart window according to claim 17 applied to at least one of a front window, a rear window, a side window, a sunloop window, and an interior partition.
20. A wearable device comprising the smart window of claim 17.
21. 18. An architectural fixture comprising the smart window of claim 17.